Resources in vulnerable young adults: self-assessments during preventive consultation with their general practitioner in Denmark. (21st November 2019) - Freund, Kirsten Schierup; Guassora, Ann Dorrit; Hegelund, Trine; Hvas, Lotte; Lous, Jørgen
Abstract: Inequality in health is increasing. People with many problems often lack energy to improve well-being and reduce their problems. This study analyses how psycho-socially challenged younger (20- to 44-year-old) patients described their own resources to reach lifestyle goals or alter life circumstances. Within the context of a randomized controlled trial, Danish participants had two structured preventive person-centred consultations with their general practitioner. Consultations focused on well-being, salutogenesis, resources, barriers and support of autonomy. Using the qualitative method: Systematic Text Condensation, we made thematic cross-analysis of patients' goal-specific resource statements described at the first consultation. Of the 209 patients, 191 (91%) chose one or two goals for a better life next year; nearly all (179) could recall and describe which resources they would use to reach their goal. We categorized resource statements into (i) personal constitution as 'willpower' and 'tenacity'; (ii) network, e.g. family; (iii) personal experience with identical or similar problems. Some patients needed to free up resources by handling psychological problems before being able to focus on lifestyle goals. The study demonstrates that patients with particular psycho-social problems could describe essential resources in a structured, salutogenic, preventive consultation with their general practitioner. Reflecting intrinsic and extrinsic motivation, these resources reflected dimensions of essential health theories like sense of coherence, self-efficacy and self-determination theory. Increased awareness of these resources seems essential for vulnerable patients by improving psychological well-being and optimism, thereby facilitating health-related changes. This may be an important step to reducing inequality in health.